Dewetting of polymer thin films on modified curved surfaces: preparation of polymer nanoparticles with asymmetric shapes by anodic aluminum oxide templates. Issue 15 (5th April 2018) - Liu, Chih-Ting; Tsai, Chia-Chan; Chu, Chien-Wei; Chi, Mu-Huan; Chung, Pei-Yun; Chen, Jiun-Tai
Abstract : We study the dewetting behaviors of poly(methyl methacrylate) (PMMA) thin films coated in the cylindrical nanopores of anodic aluminum oxide (AAO) templates by thermal annealing. Abstract : We study the dewetting behaviors of poly(methyl methacrylate) (PMMA) thin films coated in the cylindrical nanopores of anodic aluminum oxide (AAO) templates by thermal annealing. Self-assembled monolayers (SAMs) of n -octadecyltrichlorosilane (ODTS) are introduced to modify the pore surfaces of the AAO templates to induce the dewetting process. By using scanning electron microscopy (SEM), the dewetting-induced morphology transformation from the PMMA thin films to PMMA nanoparticles with asymmetric shapes can be observed. The sizes of the PMMA nanoparticles can be controlled by the original PMMA solution concentrations. The dewetting phenomena on the modified nanopores are explained by taking into account the excess intermolecular interaction free energy (Δ G ). This work opens a new possibility for creating polymer nanoparticles with asymmetric shapes in confined geometries.